Study on the Clinical Effectiveness of Comprehensive Anesthesia Nursing in Clinical Anesthesia Practice (Journal of Global Humanities and Social Sciences, 2024)
Objective: to investigate the application mode and effect of a comprehensive anesthesia nursing program in clinical anesthesia patient care intervention. Methods: 40 cases of surgical treatment patients admitted to our hospital during the period from December 2022 to December 2023 were selected as research subjects, and were divided into 20 cases of the reference group and 20 cases of the experimental group according to the principle of random allocation. For the patients in the reference group, the conventional nursing mode was implemented, and for the patients in the experimental group, the comprehensive anesthesia nursing mode was implemented. The anesthesia time and operation time of the two groups were compared. Results: the anesthesia time of patients in the experimental group was (9.5±4.0) min, which was shorter than the anesthesia time of patients in the reference group (14.3±4.3) min; the operation time of patients in the experimental group was (195.5±13.6) min, which was shorter than the operation time of patients in the reference group (234.7±12.1) min, and the difference between the two groups was significant, with a difference of P＜0.05. Conclusion: When implementing clinical anesthesia in patients undergoing surgery, it is necessary to formulate a comprehensive anesthesia care model. Conclusion: when implementing clinical anesthesia, it is necessary to develop a comprehensive anesthesia nursing program to enhance the nursing effect and improve the postoperative recovery of patients.